Effects of Distance Learning in the Teaching Performance of Senior High School Teachers at Bestlink College of the Philippines A.Y. 2021 - 2022: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Distance learning is one type of learning modality introduced during this pandemic. It comprises different modalities based on their situation - online learning, modular, E-learning, etc. The most common modality is online learning. An Online class is a platform used by teachers and students. It serves as an avenue for providing and receiving informative knowledge online. They use various apps to make it happen, such as Google Meet, Zoom, Messenger, and Discord. It is commonly known as distant learning, intended to reach out and connect with the teachers and peers. That means learners with different abilities have the opportunity to understand the course in detail. Likewise, online class has also brought convenience to educators and learners because they don’t need to spend much for transportation since distance learning takes place online. In an online class, the teachers tend to face various problems that affect the performance of the secondary teachers. It includes the following: lack of resources, which means some of our educators don’t have the gadgets or tools needed in an online class. Second, unstable network connectivity can affect the teachers' performance if this problem occurs often because they cannot perform their best due to a lagging internet connection. Lastly, Lack of Expertise using an online platform. It simply means that some of our teachers do not know how to use the different apps related to online classes. They need further assistance to perform well.The researchers developed this study to determine the effects of distance learning on the performance of Senior High School teachers at Bestlink College of the Philippines during this pandemic A.Y 2021-2022. The Descriptive Design will be used in this research. Thirty (30) Senior High School Teachers at Bestlink College of the Philippines served as respondents to answer our survey questionnaire. The sampling technique that we used is a random sampling technique to ensure a fairly equal representation of the variable for the study. The main instruments used by the researchers in this study are the questionnaires of this thesis: Part I: Profile of the Respondents and Part II: The questionnaire proper. The researchers constructed the questionnaire, identified the variables and indicators to be used, and scrutinized literature and studies related to the study. To ensure the instrument's reliability, the Research Adviser and the Dean of College Education validated and checked the questionnaire. The researchers asked permission from the Principal/CTE Dean of Bestlink College of the Philippines, Milagros O. Luang Ed.D., to collect the necessary data. The raw data were carefully reviewed, tallied and analyzed.